Un mal intolérable : revendiquer des services en santé mentale pour la jeunesse franco-ontarienne avant la crise de l’Hôpital Montfort - Arsenault, Mathieu; Martel, Marcel (Minorités linguistiques et société, 2018)
Dans les années 1970, la question de l’accès aux soins de santé mentale en français pour la minorité francophone émerge dans l’espace ontarien, notamment grâce aux pressions de l’ACFO et au rapport Dubois sur les services de santé en français. Dès lors, la question des soins de santé mentale pour la jeunesse constitue un aspect crucial de la bataille pour l’accès à des soins de santé en français. Symbole par excellence du sujet minoritaire, le jeune Franco-Ontarien s’impose comme catalyseur du discours de la classe politique, des groupes d’intérêts et des parents qui écrivent au ministre provincial de la Santé pour revendiquer des services de santé mentale en français et pour réclamer la mise en place d’une politique-cadre en matière de santé. Mots-clés : santé mentale, jeunesse, Franco-Ontarien, services en français, correspondance

Les services en santé mentale pour les jeunes francophones de la région d’Ottawa - Audet, Marie-Pier; Drolet, Marie (Reflets, 2014)

Odds of anxiety and depression symptoms in school-aged children from official language minority communities - Dupuis, Jérémie B.; Bourque, Jimmy; El Adlouni, Salah-Eddine (Frontiers in Public Health, 2021)
Objectives: The aim of this paper is to assess the odds of suffering from anxiety or depression symptoms based on the presence of certain determinants of health for youth living in the province of New Brunswick, Canada, and in two linguistically different Official Language Minority Communities (OLMCs) in the same province. Methods: With a sample of 22,329 students from grades 7 to 12 in the province of New Brunswick, Canada, logistic regressions were performed to assess each determinant of health's effect on symptoms of anxiety and depression. Results: Some social determinants, like family support, social support and food insecurity, were identified as important determinants of mental health status regardless of linguistic group membership or community membership, while other determinants, such as alcohol use, cannabis use and natural environment, were more prominent in one OLMC than the other. Discussion: Social psychology and public health theories are used in an attempt to explain the results. Limitations and recommendations are also brought forward.